HAM: Prespektif Hukum Dan Etika Dalam Kebebasan Berekspresi Dalam Sosial Media Bagi Mahasiswa - Iqmal Hakim; Aghnia Nurmaulid; Dhea Suci Wulandari; Muhammad Aswaeni Muldea (International Forum of Researchers and Lecturers, 2024)
Freedom of expression on social media for university students has complex implications and needs to be well considered. This research uses a combination approach of literature review, surveys, interviews, and content analysis to explore the legal and ethical perspectives on freedom of expression in social media for university students. The results show that freedom of expression on social media can affect the relationship between students and the government, have a great influence on social change, and produce positive impacts for students. However, students also face many challenges in the freedom of expression on social media, such as the threat of slander, online hatred, and other bad influences. Based on the research findings, we recommend increasing digital literacy and awareness of online ethics for university students. In addition, there needs to be clear and firm regulations to protect freedom of expression on social media, but also prevent violations of the law and ethics. In conclusion, students' freedom of expression in social media has complex implications, requiring a deep understanding of both legal and ethical perspectives. Universities need to play a role in providing digital ethics education to students to ensure responsible use of social media in line with Pancasila values. Thus, this study contributes to the understanding of the complexities and challenges faced by university students in exercising freedom of expression in social media.